أثر عمليات إدارة المعرفة في تحسين جودة خدمات النقل دراسة ميدانية بمؤسسة استغلال الترامواي –سيترام قسنطية- The impact of knowledge management processes in improving the quality of transport services - study field in the Corporation of Tramways Exploitation - بلمرابط شهيناز; فريمش مليكة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
تبحث هذه الدراسة عن مدى تأثير عمليات إدارة المعرفة في تحسين جودة خدمات النقل بمؤسسة استغلال الترامواي -سيترام قسنطينة-، ولهذا السبب تفترض هذه الدراسة أنه يوجد أثر إيجابي لعمليات إدارة المعرفة في تحسين جودة خدمات النقل من خلال دراسة الحالة الخاصة بنا، وقد تم استخدام الاستبيان وتوزيعيه على عينة من الموظفين وقد خلصت الدراسة بعد المعالجة بواسطة برنامج التحليل الإحصائي SPSS الى انه يوجد علاقة ارتباط أثرية بين عمليات إدارة المعرفة وتحسين جودة خدمات النقل في المؤسسة. Abstract: This study examines the impact of knowledge management processes in improving the quality of transport services at the Tramway Exploitation Corporation - Setram Constantine. Therefore, the hypothesis assumes that knowledge management processes have a positive impact in improving the quality of transport services through studying our case. The questionnaire was used and distributed to a sample of employees. Thus, the study after a processing by the Statistical Analysis Program (SPSS) concluded that there is a correlation impact between knowledge management processes and the quality of transport services in the corporation